HIPGEN: a randomized, multicentre phase III study using intramuscular PLacenta- eXpanded stromal cells therapy for recovery following hip fracture arthroplasty. (2022) - Winkler, T.; Costa, M. L.; Ofir, R.; Parolini, O.; Geissler, S.; Volk, H- D.; Eder, C.
No abstract available